TREM2 Regulates Heat Acclimation-Induced Microglial M2 Polarization Involving the PI3K-Akt Pathway Following EMF Exposure - He, Gen-Lin; Luo, Zhen; Shen, Ting-Ting; Wang, Ze-Ze; Li, Ping; Luo, Xue; Yang, Ju; Tan, Yu-Long; Wang, Yuan; Gao, Peng; Yang, Xue-Sen (Frontiers in Cellular Neuroscience, 2020)
The function of triggering receptor expressed on myeloid cells-2 (TREM2) has been described within microglia with a beneficial activated phenotype. However, the role of TREM2 underlying microglial phenotypic alterations in the cross-tolerance protection of heat acclimation (HA) against the inflammatory stimuli electromagnetic field (EMF) exposure is less well known. Here, we investigated the TREM2-related signaling mechanism induced by HA in EMF-stimulated N9 microglial cells (N9 cells). We found that EMF exposure significantly increased the production of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α, IL-1β, and IL-6), and the expression of M1 markers (CD11b and CD86); meanwhile, decreased the levels of anti-inflammatory cytokines (IL-4 and IL-10) and the expression of M2 markers (CD206 and Arg1) in N9 cells. Clearly, HA treatment decreased the secretion of TNF-α, IL-1β and IL-6 and the expression of CD11b and CD86, and enhanced the production of IL-4 and IL-10 and the expression of CD206 and Arg1. Moreover, TREM2 esiRNA and selective inhibitor of PI3K clearly decreased anti-inflammatory cytokines production, M2 markers expression, and phosphorylation of PI3K and Akt following HA plus EMF stimulation. These results indicate that TREM2 and PI3K-Akt pathway are involved in the cross-tolerance protective effect of HA in microglial polarization towards the EMF exposure. This finding inspires future studies that aim to explore the non-drug approaches underlying EMF stimulation and other central nervous system (CNS) inflammatory diseases.